Measurement of tax effort in India: An inter-state analysis (International Journal of Scientific Research and Management (IJSRM), 2017)
In the wake of fiscal crisis in recent years, most of the state governments have increasingly began to restructure their tax system to seek higher revenue or to improve the taxable capacity or tax efforts to counter balance the ever increasing public expenditures. A proper evaluation of the tax efforts of the states is required for the formulation of suitable and rational criteria for resource transfers from the centre to the states and to encourage the states to mobilize the resources for development plans from their own sources. Therefore, the examination of tax efforts of the states is important because it indicates the extent to which a state has been able to extract the resources out of its capacity. This study aims at estimating tax efforts and taxable capacity of the states in India. This exercise covers 14 major Indian states. Taxable capacity is the predicted tax-to-GDP ratio calculated using the estimated coefficients of a regression specification. In this study, tax ratio is regressed on the two capacity factors, per capita income and percentage of non-agricultural sector income in the state income Tax effort is the index of the ratio between the share of the actual collection to NSDP and the predicted taxable capacity. On the basis of tax effort index, states have been classified into three groups- high tax effort, good tax effort and low tax effort. The states have also been ranked on this basis. The findings of the study indicated that less-developed state like Bihar, Madhya Pradesh, and Rajasthan were raising more than their capacity, while West Bengal, Gujarat, Punjab and Haryana were making lower tax effort, i.e. their tax effort has not been able to sufficiently exploit its estimated tax potential.